Incorporating a “Better” Behavioral Bias for Both Consumers and Firms in Rebate Programs - Chung, Kevin (Management Science, 2020)
We study a rebate program in the credit card industry where the firm automatically processed the rebate earned by consumers with flexible and effortless redemption opportunities in future transactions. Contrary to what the normative economic theory would predict, we document that consumers frequently failed to redeem their rebate. Given this observation, we examine what may have been the primary driving force behind this pattern and the implications for the firm. We provide evidence that the phenomenon that we observe in our study is a result of cardholders being influenced by the way their outcomes were framed. We find that redemption incidences coincide with episodes where rebates are a larger portion of the amount spent. On the basis of the empirical regularities, we formulate a model of cardholder behavior where the cardholder experiences increasing psychological utility when rebate redemption yields a deeper discount. The model estimates indicate that, although delayed redemption left customers monetarily worse off in each transaction (cardholders passed up on average $0.76 of card-level benefits to experience greater psychological utility), once the psychological utility is taken into account, customers were shown to fare better overall. For the firm, in addition to the card benefits that were passed up, the psychological utility generated an additional average benefit of $1.21 per redemption. Finally, through counterfactuals we show that carefully designing a rebate program that takes into account consumers’ psychological redemption utility can further benefit both consumers and firms. This paper was accepted by Juanjuan Zhang, marketing.